TINJAUAN YURIDIS TEMBAK DITEMPAT YANG DILAKUKAN OLEH PIHAK KEPOLISIAN TERHADAP PELAKU TINDAK PIDANA DIKAITKAN DENGAN ASAS PRADUGA TAK BERSALAH - Irfan Yobel Halomoan Sinaga; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Shoot place is a term often used by the media or the public against the police conducting an action in the form of a shot against the suspect. The term in the police shoot on sight known as a decisive action, where decisive action in the form of action shoot on sight. While the presumption of innocence is any person suspected, arrested, detained, prosecuted, and / or confronted in the face of the trial court shall be presumed innocent until the court ruling that declared his guilt and permanent legal power.Based on this understanding, the authors formulated two formulation of the problem, namely: First, How About Setting Shoot place that Forum by The Police. Second, How to Shoot Relevance place that Done By The Police With the principle of Presumption of Innocence.This type of research can be classified in normative law research (legal research) or also called the research literature, the research done with normative juridical approach under study is library materials or secondary data, which consists of primary legal materials, secondary law, and tertiary legal materials, data sources used, the secondary data. Data collection techniques used in the writing of this research is to use the method of assessment literature or documentary studies.From the research problem there are two main things that can be summed up as follows: First, the use of firearms are the last to be done by the police to discontinue the offender or alleged offender. Thus, the use of firearms by police is only used when the threat to human life. Before using firearms, the police must give a clear warning and should always be guided by the rules and regulations. Second, Catching up with ways to shoot or physical violence against suspects obviously had ignored the presumption of innocence. Despite the evidence that is the basis for the police to make arrests have led to the criminal suspect, but their guilt has not been proven through the courts. Lack of understanding by the police to the presumption of innocence in arresting the perpetrators to be one cause.Keywords: Shoot place – Police- Principle of Presumption of Innocence